Action Plans in Asthma. Issue 6 (2006) - Beauchesne, Marie-France; Levert, Valérie; Tawil, Miray El; Labrecque, Manon; Blais, Lucie
Abstract : BACKGROUND: Action plans are recommended for most patients with persistent asthma to reduce the morbidity associated with this chronic disease. Unfortunately, despite these recommendations, this tool remains underused. METHODS: The authors conducted a descriptive study at the asthma clinic of a tertiary care centre to determine the number of asthmatic patients presenting to a respiratory physician (new reference or follow-up visit) who possessed an individualized, written action plan, and to evaluate the patients' level of confidence and perceived efficacy toward their plans. In addition, for all patients in the study, the level of confidence in and the perceived efficacy of three different action plans (two traditional tools versus a simplified tool) were compared. RESULTS: A total of 92 asthmatic patients were included in the study. Overall, 46% of the patients possessed an action plan. The patients' average level of confidence and perceived efficacy toward their action plans were high (4.1 out of five and 3.3 out of four, respectively). When the three different action plans were compared, the level of confidence in and perceived efficacy of the traditional tools were similar, both being superior to the simplified tool. CONCLUSION: The number of asthmatic patients who presented to the asthma clinic and who possessed an action plan was higher than the reported Canadian mean of 10%; however, most of the patients were treated by specialized respiratory physicians, which may explain this improvement. Considering that most patients with persistent asthma should have an individualized, written action plan, the present study confirms that this tool is still not used for all asthmatic patients.